Outdoor luminescence imaging of field-deployed PV modules. (1st October 2022) - Kunz, Oliver; Schlipf, Jan; Fladung, Andreas; Khoo, Yong Sheng; Bedrich, Karl; Trupke, Thorsten; Hameiri, Ziv
Abstract: Solar photovoltaic (PV) installations have increased exponentially over the last decade and are now at a stage where they provide humanity with the greatest opportunity to mitigate accelerating climate change. For the continued growth and success of PV energy the reliable inspection of solar power plants is an important requirement. This ensures the installations are of high quality, safe to operate, and produce the maximum possible power for the longest possible plant life. Outdoor luminescence imaging of field-deployed PV modules provides module image data with unparalleled fidelity and is therefore the gold standard for assessing the quality, defect types, and degradation state of field-deployed PV modules. Several luminescence imaging methods have been developed and some of them are already routinely used to inspect solar power plants. The preferred luminescence inspection method to be used depends on the required image resolution, the defect types that need to be identified, cost, inspection throughput, technological readiness, and other factors. Due to the rich and detailed information provided by luminescence imaging measurements and modern image analysis methods, luminescence imaging is becoming an increasingly important tool for PV module quality assurance in PV power plants. Outdoor luminescence imaging can make valuable contributions to the commissioning, operation, and assessment of solar power plants prior to a change of ownership or after severe weather events. Another increasingly important use of these technologies is the cost-effective end-of-life assessment of solar modules to enable a sustainable circular economy.